Growth and earnings persistence in banking firms a dynamic panel investigation - Shehzad, Choudhry Tanveer; Haan, Jakob de 1960-; Scholtens, Bert (CESifo, 2009)
This paper investigates (i) whether growth and profitability persist in banking firms, (ii) whether the level and volatility of growth and profitability are bank-size dependent, and (iii) the relationship between growth and profitability of a bank. Using a dynamic panel model estimated by GMM for a mixed sample of more than 1500 banks from 65 countries, we find no evidence of persistence in bank growth. However, our findings suggest significant persistence in bank profitability. Moreover, our results show that the growth and profitability dynamics of banks based in OECD countries differ from those of banks in non-OECD countries. -- bank size ; bank earnings ; earnings volatility ; bank risk ; Gibrat's law
Keywords: Marktrisiko; Bank; Unternehmenswachstum; Gewinn; Unternehmensgröße